The Influence of Prudence and Financial Distress on Tax Avoidance in Food and Beverage Sub-Sector Manufacturing Companies in Indonesia - Yoan Yohana Tallane; Nelcie Valensya Mussa; Sara Monica Tarigan (Jurnal Ekonomi, 2024)
The growth in state revenues which is expected to be contributed from the taxation sector, which is the largest source of income for Indonesia in 2020-2022, indirectly shows the increasing dependence of the Indonesian economy on revenues originating from this sector for the implementation of national development. However, this has not been balanced with citizens' awareness of paying taxes. For companies, tax is seen as a burden that will reduce net profit, so companies tend to practice tax avoidance to reduce the size of their tax burden. The practice of tax avoidance can be carried out by using management policies in the practice of prudence, where in this principle, the company practices the principle of prudence by delaying income and accelerating the recognition of expenses, resulting in lower net profits. The condition of manufacturing companies in the food and beverage sub-sector in 2020-2022 which was affected by Covid-19 with a decline in sales is one of the early indications of financial distress, which can encourage companies to carry out tax avoidance practices in order to reduce the tax burden that must be paid. Therefore, this research examines the influence of the relationship between prudence and financial distress on tax avoidance in manufacturing companies in the food and beverage sub-sector.